A REVIEW ON AGENTS FOR THE TREATMENT OF LEPROSY INFECTION - HABIBALLA AHMED, MUHANAD MOHAMED; ANURADHA; WADHWA, PANKAJ (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Leprosy is an ancient disease which is caused due to bacterial infection while curable but endures to be a substantial health problem in numerous parts across the world. It is an extremely contagious disease that is caused by any of 3 strains of bacteria such as Mycobacterium tuberculosis; Nontuberculous Mycobacterium; and Mycobacterium leprae. In several regions of Brazil, leprosy is a health issue which is still an endemic. Mainly skin, peripheral nerves, eyes, and mucosa of the upper respiratory tract are affected due to this chronic infection. As per the data shared by WHO across 159 countries globally, there were around 208,619 new leprosy cases reported. The global prevalence of leprosy is overcome with the aid of multidrug therapy which remains to be the chiefly targeted for treatment. The multidrug therapy gets attention as they show tremendous potential in fighting this disease. This review briefs about the different drugs and strategies which are used in treatment and superintendence of leprosy.